THE IMPORTANCE OF THE DISSEMINATION OF SIGN LANGUAGE (LIBRAS) RURAL AREA COMMUNITY - Regina Miranda, Larissa (Revista Gênero e Interdisciplinaridade, 2022)
This article aims to present the importance of the dissemination of sign language (libras) in the rural community. sign language is a spatial viso language and is presented in a different modality of the oral language, since it uses vision and space, and not the oral-auditory canal, that is, speech. sign language makes use of body and facial movements and expressions that are perceived by vision. Education in the rural area is considered a new research, when deaf people living in the rural city who used the natural language as the acquisition of the language of images, forms, places, for example. It is they who create their own sign language in the rural town, so other people are unable to communicate right with others because of different sign language. instructors or teachers can perceive and have to accept respect for sign language used by deaf people living in the countryside. For the construction of this research, we used institutional documents, scientific articles, master’s dissertations, doctoral theses and videos available on the Internet about the importance of sign language in the rural community. The methodology adopted is based on a field research and analysis of the data collected, which were collected through the interview conducted by the zoom platform with a teenage resident of rural areas, without knowledge, until then, of the pounds or Portuguese writing. It is necessary to be aware of the importance of the dissemination of sign language in the rural area, because it provides opportunities for the possibility of exchanging information in their own language with the community and for them to take on their identity as a deaf subject who has his own way of communicating, interacting, perceiving and knowing the world.